Power relations and dual office-holding practices in Indonesia from an Islamic political ethics perspective - Frans Tory Damara Pradipta; Subri Rahmadani (Privietlab, 2026)
This article examines power relations and the practice of dual office-holding (rangkap jabatan) from the perspective of Islamic political ethics. In contemporary political governance, the accumulation of authority through concurrent positions has become a recurring issue, raising ethical concerns related to conflicts of interest, accountability, and the concentration of power. Islamic political ethics, as articulated in classical and modern Islamic political thought, emphasizes justice (ʿadl), trust (amānah), and the moral responsibility of political actors to prioritize public welfare over personal or group interests. This study employs a qualitative literature-based method, drawing on classical Islamic political texts, contemporary scholarly works, and recent governance discourses in Indonesia. The analysis shows that the practice of dual office-holding tends to weaken institutional balance and contradicts core ethical principles in Islamic political thought, particularly those related to responsibility, transparency, and the prevention of power abuse. The study argues that Islamic political ethics offers a relevant normative framework to critically assess power relations and to address ethical challenges in modern governance. Integrating these ethical principles can contribute to strengthening political accountability and public trust within democratic systems.